Mapping of the educational status of Haryana based on location quotient - Ashwani (National Geographical Journal of India, 2023)
India has the world’s second-largest educational system. The Indian educational system has seen significant changes. A lot of work has gone into shaping the current educational system. The announcements included the elimination of mandatory CBSE board examinations for class 10th beginning in the 2010-11 school year, and the implementation of a grading system, after the passage of the Right of Children to Free and Compulsory Education Bill. Haryana is the state that contributes 3.7 percent of India’s overall GDP. The purpose of this research is to shed light on Haryana’s educational system, as well as to examine several other sectors. This document is both qualitative and quantitative in character, and it is based on information gathered from several government websites as well as reports from the Planning Commission, the Government of Haryana, and the Government of India. All the districts of the region are divided into three categories on the basis of the composite index of each of the districts. Districts having the highest composite index are Karnal and Yamuna Nagar while Panchkula has the lowest composite index. The rest of the districts depicts a moderate picture. Ambala and Kaithal regions have higher composite indexes as these districts are more urbanized and people of these districts are more education conscious.